Guidance for switching from off-label antipsychotics to pimavanserin for Parkinson's disease psychosis: an expert consensus. (27th December 2018) - Black, Kevin J.; Nasrallah, Henry; Isaacson, Stuart; Stacy, Mark; Pahwa, Rajesh; Adler, Charles H.; Alva, Gustavo; Cooney, Jeffrey W.; Kremens, Daniel; Menza, Matthew A.; Meyer, Jonathan M.; Patkar, Ashwin A.; et al.
Abstract : Patients with Parkinson's disease psychosis (PDP) are often treated with an atypical antipsychotic, especially quetiapine or clozapine, but side effects, lack of sufficient efficacy, or both may motivate a switch to pimavanserin, the first medication approved for management of PDP. How best to implement a switch to pimavanserin has not been clear, as there are no controlled trials or case series in the literature to provide guidance. An abrupt switch may interrupt partially effective treatment or potentially trigger rebound effects from antipsychotic withdrawal, whereas cross-taper involves potential drug interactions. A panel of experts drew from published data, their experience treating PDP, lessons from switching antipsychotic drugs in other populations, and the pharmacology of the relevant drugs, to establish consensus recommendations. The panel concluded that patients with PDP can be safely and effectively switched from atypical antipsychotics used off label in PDP to the recently approved pimavanserin by considering each agent's pharmacokinetics and pharmacodynamics, receptor interactions, and the clinical reason for switching (efficacy or adverse events). Final recommendations are that such a switch should aim to maintain adequate 5-HT2A antagonism during the switch, thus providing a stable transition so that efficacy is maintained. Specifically, the consensus recommendation is to add pimavanserin at the full recommended daily dose (34 mg) for 2–6 weeks in most patients before beginning to taper and discontinue quetiapine or clozapine over several days to weeks. Further details are provided for this recommendation, as well as for special clinical circumstances where switching may need to proceed more rapidly.